2004
DOI: 10.1007/s10564-004-2304-6
|View full text |Cite
|
Sign up to set email alerts
|

Athero-express: Differential atherosclerotic plaque expression of mRNA and protein in relation to cardiovascular events and patient characteristics. Rationale and design

Abstract: In clinical practice, biological markers are not available to routinely assess the progression of atherosclerotic disease or the development of restenosis following endarterectomy or catheter based interventions. Endarterectomy procedures provide an opportunity to study mechanisms of restenosis and progression of atherosclerotic disease since atherosclerotic tissue is obtained. Athero-Express is an ongoing prospective study, initiated in 2002, with the objective to investigate the etiological value of plaque c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
334
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 211 publications
(336 citation statements)
references
References 24 publications
0
334
0
Order By: Relevance
“…We previously hypothesized and confirmed that a local plaque can carry information about the systemic vascular status of a patient 10,14,20 and specifically that PH in carotid plaques is predictive for events in all vascular territories. 10 In the current study, we demonstrate that, independent of cardiovascular risk factors and symptom status before CEA, PH does not predict outcome in women, whereas in men, PH predicts a substantially and significantly increased risk of an event in any vascular territory after CEA.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We previously hypothesized and confirmed that a local plaque can carry information about the systemic vascular status of a patient 10,14,20 and specifically that PH in carotid plaques is predictive for events in all vascular territories. 10 In the current study, we demonstrate that, independent of cardiovascular risk factors and symptom status before CEA, PH does not predict outcome in women, whereas in men, PH predicts a substantially and significantly increased risk of an event in any vascular territory after CEA.…”
Section: Discussionmentioning
confidence: 77%
“…14 In summary, all patients undergoing CEA at the University Medical Center, Utrecht, and St Antonius Hospital, Nieuwegein, the Netherlands, were asked to participate consecutively during the study period. There were no exclusion criteria.…”
Section: Patient Selectionmentioning
confidence: 99%
“…16 Medical ethics boards of the 2 participating hospitals (University Medical Center Utrecht and St Antonius Hospital Nieuwegein, The Netherlands) approved the study. All participating patients provided written informed consent.…”
Section: Methods Study Populationmentioning
confidence: 99%
“…These tandem temporal changes in coronary and cerebral events suggest a systemic rather than a local change in atherosclerotic disease progression. Athero-Express, an ongoing Dutch study, has collected atherosclerotic carotid plaques since 2002 64 . Analyses of retrieved atherosclerotic plaque specimens in the Athero-Express biobank have revealed a clear shift in the characteristics of human atherosclerotic plaques over time 65 ascribed to "stable" plaques occurred in lesions retrieved from either symptomatic or asymptomatic patients.…”
Section: Time Dependent Changes In Plaque Characteristics That Underlmentioning
confidence: 99%